Pengaruh Zumba terhadap Tingkat Nyeri Muskuloskeletal pada Ibu Rumah Tangga di Grand City Mall Surabaya - Mufidah, Hania; Kurnia, Rina (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Abstract Background: The housewives are very productive an important role in managing the needs of the house and family so that it requires a lot of energy and time. The activities of housewives can cause complaints of musculoskeletal pain due to non-ergonomic positions for a long time and repeatedly. Zumba serves to reduce musculoskeletal pain due to improper static position and repetitive pressure (stress). Objective: This study aims to determine the effect of zumba exercise on the level of musculoskeletal pain in housewives at Grand City Mall Surabaya. Method: This research is a quantitative study with a pre-experimental design with one group prettest-posttest type. The sampling technique used is purposive sampling, involving 20 samples. Using the Nordic Body Map instrument with 27 locations of body pain. The Zumba intervention was performed 8 times for 45 minutes in 4 weeks. Normality test using Shapiro Wilk and hypothesis testing using Paired Sample Test. Results: The research sample was women involving 20 samples with the dominated of the early elderly (75%) with medium tenure (45%). Normality test results obtained normal data. Paired test p = 0.001 which means p-value < (0.05) which mean can be concluded that there is an effect of Zumba on the level of musculoskeletal pain in housewives at Grand City Mall Surabaya. Conclusion: There is an effect of Zumba on the level of musculoskeletal pain in housewives at Grand City Mall Surabaya. Keywords: Zumba, musculoskeletal, housewives.